2017
DOI: 10.1097/rct.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and Magnetic Resonance Imaging Characteristics of Peripheral Primitive Neuroectodermal Tumor

Abstract: Peripheral primitive neuroectodermal tumor should be suggested as an important differential diagnosis when the tumor presents as a large, ill-defined solid mass with aggressive extension and significant enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…About MRI features from diploe and dura metastases, the literature indicates that these usually devises low to intermediate signal intensity on both T1W and T2W, as in the present case. Additionally, an avid enhancement after gadolinium administration and restricted diffusion was noticed [33][34][35]. According with Saifuddin et al soft tissue masses are seen in 87% of the reported cases with diploe affectation.…”
Section: Discussionmentioning
confidence: 86%
“…About MRI features from diploe and dura metastases, the literature indicates that these usually devises low to intermediate signal intensity on both T1W and T2W, as in the present case. Additionally, an avid enhancement after gadolinium administration and restricted diffusion was noticed [33][34][35]. According with Saifuddin et al soft tissue masses are seen in 87% of the reported cases with diploe affectation.…”
Section: Discussionmentioning
confidence: 86%